2009
DOI: 10.1002/cyto.b.20496
|View full text |Cite
|
Sign up to set email alerts
|

Variability of CD3 membrane expression and T cell activation capacity

Abstract: Background: abT cells have a wide distribution of CD3 membrane density. The aim of this article was to evaluate the significance of the CD3 differential expression on T cell subsets. Analysis was performed on healthy donors and renal transplant patients by flow cytometry. The results obtained are: (1) CD3 expression was widely distributed (CV 5 38.3 6 3.1 to 43 6 2.3%). (2) The CD4, CD8, CD45 and forward scatter were similarly distributed. (3) The diversity of CD3 expression was directly related to the clonoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 42 publications
8
48
0
Order By: Relevance
“…They showed that human CD8 + T cells express the lowest amounts of CD3 and TCRgd + T cells express the highest amounts. However, these previous studies did not report that CD3 heterogeneity determined biologically significant outcomes either in vitro or in vivo (15,16 (34). A parallel and associated finding was that Th17 T cell clones responded less to in vitro TCR stimulation than did Th1 T cell clones (34).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…They showed that human CD8 + T cells express the lowest amounts of CD3 and TCRgd + T cells express the highest amounts. However, these previous studies did not report that CD3 heterogeneity determined biologically significant outcomes either in vitro or in vivo (15,16 (34). A parallel and associated finding was that Th17 T cell clones responded less to in vitro TCR stimulation than did Th1 T cell clones (34).…”
Section: Discussionmentioning
confidence: 96%
“…To our knowledge, our present study investigated a critical issue with depth: we tested both mouse and human samples; we examined a wide range of T cell subsets; and, perhaps most importantly, we used an unbiased approach for flow cytometry data analysis. Differences in CD3 expression on human CD4 + , CD8 + , and TCRgd + T cell subsets were described for the first time by the groups of Lambert and Genin (15) and El Hentati et al (16). They showed that human CD8 + T cells express the lowest amounts of CD3 and TCRgd + T cells express the highest amounts.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…[15][16][17][18] These models were cast as ordinary differential equations by representing the kinetics of the biochemical reactions. [19][20][21][22] A more sophisticated approach considers the dynamics of cell population, where each cell is characterized by the concentration of one or several proteins. This leads to a multi-dimensional population balance equation with the order depending upon the number of internal variables (protein concentrations).…”
Section: Introductionmentioning
confidence: 99%